2016
DOI: 10.1111/lam.12614
|View full text |Cite
|
Sign up to set email alerts
|

Are natural reservoirs important for cholera surveillance? The case of an outbreak in a Brazilian estuary

Abstract: Despite most of the cholera cases that occurred in Brazil during the 7th pandemic were located in the northern areas of the country, a significant outbreak in Paranaguá, an estuary in the south coast, resulted in at least three deaths in 1999. We report here the detection of Vibrio cholerae O1 in water, zooplankton and bivalve samples during the outbreak, using direct fluorescence assay as an alternative method for the traditional plate culture employed at the time by the Brazilian Sanitary Agency. Results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Many parasites with 'environmental' transmission may be vectored by other microorganisms with which they interact during an environmental phase. Examples include the relationships between copepods and V. cholerae [197], or amoebae and bacteria such as Francisella tularensis [198], Legionella pneumophila [199], Y. pestis [200] and B. anthracis [178]. Thus, we may be biased by instinctively considering macroscopic secondary hosts, vectors and interactions in a different evolutionary light than non-mammalian 'secondary hosts' and non-arthropod 'vectors' where the mutualists/antagonists are chiefly other microorganisms.…”
Section: Methodological Developmentsmentioning
confidence: 99%
“…Many parasites with 'environmental' transmission may be vectored by other microorganisms with which they interact during an environmental phase. Examples include the relationships between copepods and V. cholerae [197], or amoebae and bacteria such as Francisella tularensis [198], Legionella pneumophila [199], Y. pestis [200] and B. anthracis [178]. Thus, we may be biased by instinctively considering macroscopic secondary hosts, vectors and interactions in a different evolutionary light than non-mammalian 'secondary hosts' and non-arthropod 'vectors' where the mutualists/antagonists are chiefly other microorganisms.…”
Section: Methodological Developmentsmentioning
confidence: 99%
“…Studies conducted elsewhere (e.g., Asia and South America) show that brackish, riverine, estuarine, and coastal waters, and other physicochemical properties such as salinity promote the persistence and proliferation of V. cholerae [18]. Other studies reported complex networks of interactions between V. cholerae and sea dwellers and aquatic organisms such as bivalves and shellfish [29]. One study focusing on freshwater systems in several sites in India and Africa (Zanzibar and Malawi) showed that egg masses of chironomids, which are "non-biting midges" (Diptera Chironomidae), were infected by V. cholerae in both countries.…”
Section: Environmental Reservoirs: Where Cholera Lurks During Inter-ementioning
confidence: 99%
“…Lacking such data, several potential reservoirs could harbor cholera in SSA, including on-site sanitation systems, wetlands, landfills, heavily polluted surface aquatic systems, and groundwater systems. V. cholerae and sea dwellers and aquatic organisms such as bivalves and shellfish [29]. One study focusing on freshwater systems in several sites in India and Africa (Zanzibar and Malawi) showed that egg masses of chironomids, which are "non-biting midges" (Diptera Chironomidae), were infected by V. cholerae in both countries.…”
Section: Environmental Reservoirs: Where Cholera Lurks During Inter-ementioning
confidence: 99%
See 1 more Smart Citation
“…The Global Roadmap to 2030, was launched by the Global Task Force on Cholera Control (GTFCC Ending Cholera] to decrease death rate due to cholera by 90%, especially from at least half of the cholera-affected countries. The objectives of this roadmap are; to fortify health systems, water, sanitation and hygiene (WASH) as well as to coordinate different ways by which cholera can be controlled in these countries by 2030 [18]. This article therefore basically seeks to review the epidemiology of cholera in Nigeria, Africa and the world at large, to understand the level of spread, management and preventive measures so far implemented in these endemic regions.…”
Section: Introductionmentioning
confidence: 99%